PENERAPAN PENGGUNAAN COMFORT SCALE DI RUANG INTENSIVE CARE UNIT DI SATU RUMAH SAKIT SWASTA DI INDONESIA [IMPLEMENTATION COMFORT SCALE IN INTENSIVE CARE UNIT AT ONE PRIVATE HOSPITAL IN INDONESIA] - Dwi Christian Silitonga; Siska Natalia; Elfrida Silalahi (Universitas Pelita Harapan, 2021)
The Comfort Scale is a standard pain assessment format for measuring the level of psychological distress in critically ill patients, children under 18 years of age and adults who use sedation and are on a ventilator. This study aims to determine the application of the comfort scale in the Intensive Care Unit room. There are no research been conducted related to the application of the use of the comfort scale in a private hospital in West Indonesia. This research used quantitative descriptive with documentation study. The population in this study were patient medical records. The sampling technique used was purposive sampling and obtained a sample of 75 medical records of patients treated at the Intensive Care Unit (ICU) from January to July 2017 with a level of delirium to coma on a ventilator and using sedation drugs. The results of this study stated that out of 75 patient medical records were 11 (14.67%) the files was fill complete with the assessments comfort scale. There were four items has lower scores: crying (18.7%), body movement (28.0%), muscle tone (21.3%), facial tension (17.3%). There were 10 (13.33%) medical records for which there were no special ICU records. Recommendations for further research to carried out research in the ICU room and examining ICU nurses in conducting pain assessments so that the results of the assessment in comfort scale is accordance with all they have done.BAHASA INDONESIA Comfort Scale merupakan suatu standar format pengkajian nyeri untuk mengukur tingkat distress psikologis pada pasien kritis anak-anak dibawah usia 18 tahun dan dewasa yang menggunakan sedasi dan terpasang ventilator. Penelitian ini bertujuan untuk mengetahui penerapan penggunaan comfort scale di ruang Intensive Care Unit (ICU). Sejauh penelitian ini dilakukan, belum ada penelitian terkait penerapan penggunaan comfort scale di satu RS Swasta di Indonesia, sedangkan pendokumentasian erat kaitannya dengan kualitas pelayanan yang diberikan kepada pasien. Desain penelitian ini menggunakan deskriptif kuantitatif dengan studi dokumentasi. Populasi dalam penelitian ini adalah rekam medik pasien. Teknik pengambilan sampel yang digunakan adalah purposive sampling dan diperoleh sampel sejumlah 75 rekam medik pasien yang dirawat di ICU dari bulan Januari hingga Juli 2017 dengan tingkat kesadaran delirium sampai dengan koma yang terpasang ventilator serta menggunakan obat sedasi. Hasil penelitian ini menyatakan bahwa dari 75 rekam medik pasien terdapat 11 (14,67%) file pasien lengkap terisi pengkajian comfort scale. Ada empat item yang mendapatkan nilai rendah : tangisan (18,7%), gerakan tubuh (28,0%), tonus otot (21,3%), tegangan wajah (17,3%). Terdapat 10 (13,33%) rekam medik yang tidak terdapat catatan khusus ICU. Rekomendasi untuk penelitian selanjutnya dapat melakukan penelitian di ruang ICU dan meneliti perawat ICU dalam melakukan pengkajian nyeri sehingga hasil pengkajian comfort scale sesuai dengan yang dilakukan oleh perawat.